Islamic finance crossing the 40-years milestone – the way forward - Ayub, Muhammad (Intellectual Discourse, 2018)
Islamic finance has experienced considerable growth worldwide in terms of deposits and assets of Islamic banks over the last 40 years, but shows little signs of achieving maturity. Almost all Islamic finance products currently is use are mere replicas of their conventional counterparts. This study follows the archival research strategy of Bryman (1989), and analyses the literature on Islamic finance theory and products and practices in order to ascertain the reforms needed for the maturity goal. The paper proposes adoption of a new law regarding money, different policy approaches, new structures of finance for shifting to risk-based financing, new models, procedures and some fresh thought in order to relate banking and finance to the real economy. It recommends a leading role for Islamic economists for effective reforms in the monetary and credit system in order to ensure that all financing is based on goods, services, stocks or securities representing real assets in line with the Shariʽah principles. The suggested policy measures are expected to lead to social inclusion and harmony in the interests of all stakeholders in business and finance transactions.